External iliac artery dissection causing early renal transplant dysfunction. (2nd April 2014) - Lee, Gwyn; Barlow, Adam; Doughman, Tahir; Nicholson, Michael L
Abstract : External iliac artery dissection after kidney transplantation is a rare, catastrophic but potentially reversible complication. Treatment which may save both the transplant and the patient requires clinical suspicion, timely imaging, and prompt intervention. This case report describes successful diagnosis of this complication and surgical intervention which saved the kidney and safeguarded blood supply to the patient's leg.